La innovación como proceso y su gestión en la organización: una aplicación para el sector gráfico colombiano - Paula Viviana Robayo Acuña (Suma de Negocios, 2016)
This paper reports on the analysis of a descriptive case study carried out with a firm in the Colombian graphic arts industry. This study examined the management of the innovation process from an internal perspective in which the phenomenon of innovation is considered as a process and not as a final result. The data were gathered from a survey, an interview, and an observation work. The results revealed as main conclusion that successful management of innovation involves creating a culture related to innovation from general management, which enables companies to identify the key factors —whether internal or external— that characterize its process in the firm. Regarding this specific case, the process of innovation is informal and non-systematic. It seeks for seizing business opportunities, and it is generally originated from both the customers’ needs and demands and the reaction to circumstances induced by competition.